Comparative Analysis of Mitochondrial Genomes in Gryllidea (Insecta: Orthoptera): Implications for Adaptive Evolution in Ant-Loving Crickets. (23rd September 2021) - Sanno, Ryuto; Kataoka, Kosuke; Hayakawa, Shota; Ide, Keigo; Nguyen, Chuong N; Nguyen, Thao P; Le, Binh T N; Kim, Oanh T P; Mineta, Katsuhiko; Takeyama, Haruko; Takeda, Makio; Sato, Toshiyuki; et al.
Abstract: Species of infraorder Gryllidea, or crickets, are useful invertebrate models for studying developmental biology and neuroscience. They have also attracted attention as alternative protein sources for human food and animal feed. Mitochondrial genomic information on related invertebrates, such as katydids, and locusts, has recently become available in attempt to clarify the controversial classification schemes, although robust phylogenetic relationships with emphasis on crickets remain elusive. Here, we report newly sequenced complete mitochondrial genomes of crickets to study their phylogeny, genomic rearrangements, and adaptive evolution. First, we conducted de novo assembly of mitochondrial genomes from eight cricket species and annotated protein-coding genes and transfer and ribosomal RNAs using automatic annotations and manual curation. Next, by combining newly described protein-coding genes with public data of the complete Gryllidea genomes and gene annotations, we performed phylogenetic analysis and found gene order rearrangements in several branches. We further analyzed genetic signatures of selection in ant-loving crickets (Myrmecophilidae), which are small wingless crickets that inhabit ant nests. Three distinct approaches revealed two positively selected sites in the cox1 gene in these crickets. Protein 3D structural analyses suggested that these selected sites could influence the interaction of respiratory complex proteins, conferring benefits to ant-loving crickets with a unique ecological niche and morphology. These findings enhance our understanding of the genetic basis of cricket evolution without relying on estimates based on a limited number of molecular markers.